Ageing and the resting state: is cognition obsolete?. Issue 6 (3rd July 2017) - Campbell, Karen L.; Schacter, Daniel L.
ABSTRACT: Recent years have seen the rise in popularity of the resting-state approach to neurocognitive ageing, with many studies examining age differences in functional connectivity at rest and relating these differences to cognitive performance outside the scanner. There are many advantages to the resting state that likely contribute to its popularity and indeed, many insights have been gained from this work. However, there are also several limitations of the resting-state approach that restrict its ability to contribute to the study of neurocognitive ageing. In this opinion piece, we consider some of those limitations and argue that task-based studies are still essential to developing a mechanistic understanding of how age affects the brain in a cognitively relevant manner – a fundamental goal of neuroscientific research into ageing.